Application of Permanent Synchronous Motor Traction System in Shenyang Metro Line 2 Vehicles - YAN Lei; GUO Feng (机车电传动)
Loading project, technology and risk analysis of Shenyang metro line 2 vehicles permanent synchronous motor traction system were introduced, as well as its debugging, test and operation situation. The permanent synchronous motor traction system has the merits of stability and low cost, and has great sense to urban rail transit development.